2013
DOI: 10.1371/journal.pbio.1001750
|View full text |Cite|
|
Sign up to set email alerts
|

The Velvet Family of Fungal Regulators Contains a DNA-Binding Domain Structurally Similar to NF-κB

Abstract: This study reveals an important family of fungal regulatory proteins to be transcription factors that contain a DNA-binding “velvet” domain structurally related to that of mammalian NFkB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
206
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(209 citation statements)
references
References 55 publications
3
206
0
Order By: Relevance
“…We previously showed that VosA is a feedback negative regulator of brlA, and its velvet domain directly binds to the brlAb promoter (Ahmed et al 2013). The deletion of either vosA or nsdD caused elevated expression of brlA and formation of conidiophores in liquid submerged culture, where WT strains do not develop (Ni and Yu 2007) (Figure 6B).…”
Section: Additive Role Of Nsdd and Vosa In Repressing Conidiationmentioning
confidence: 83%
See 4 more Smart Citations
“…We previously showed that VosA is a feedback negative regulator of brlA, and its velvet domain directly binds to the brlAb promoter (Ahmed et al 2013). The deletion of either vosA or nsdD caused elevated expression of brlA and formation of conidiophores in liquid submerged culture, where WT strains do not develop (Ni and Yu 2007) (Figure 6B).…”
Section: Additive Role Of Nsdd and Vosa In Repressing Conidiationmentioning
confidence: 83%
“…Our recent studies demonstrated that VosA and VelB control expression of various genes in conidia via directly binding to the promoters of their target genes (Ahmed et al 2013). The removal of vosA causes abnormal accumulation of brlA in conidia and vegetative cells (Ni and Yu 2007;Ahmed et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations